On the use of options by mutual funds: Do they know what they are doing? - Cici, Gjergji; Palacios, Luis-Felipe (Journal of Banking & Finance, 2015)
Given recent regulatory inquiries into the derivative-trading practices of mutual funds, we examine their detailed option holdings to assess how mutual funds employ options, what funds use options, and how that affects performance and risk. Mutual funds’ use of options appears consistent with income generation and hedging motives, is systematically related to experience, education, and gender characteristics of portfolio managers, and does not lead to performance benefits, on average. Instead, certain uses of options lead to underperformance. We document no permanent or temporary aggressive risk taking by options users, finding instead that some funds use options to effectively lower risk.